3D printing and additive manufacturing for customized design : Unmanned Vehicles-Chassis parts - Ng, Jian Rui (2015)
3D printing, like its name suggests, is a process where an object is printed out by printer heads 3-dimensionally, layer by layer. Also called additive manufacturing, this process has huge potential for growth in the manufacturing industry as it provides convenient prototyping and efficient use of materials, which are only a few of its countless benefits. The project aims to harness the benefits of 3D printing in the production of an unmanned vehicle, in this case, an electronically powered remote control car, Traxxas Rally VXL (Model 7307). The main focus of this project would be on the vehicle chassis component of this remote controlled car. New designs were made and eventually fabricated in an attempt to integrate 3D printed parts into the production of this unmanned vehicle. Valuable information was collected through these processes and eventually a preferred design was chosen and the end of the project.